Faktor-faktor yang Mempengaruhi Pemanfaatan Pelayanan Kesehatan Reproduksi Remaja di Kota Jayapura - Yunita Kristina (Jurusan Biologi FMIPA Universitas Cenderawasih, 2017)
This research aimed to study the factors that affect of the adolescent reproductive health service in Jayapura Municipality. This research applied an explanatory research method with a cross-sectional approach. Data were collected by questionnaire, which were involving 393 adolescents aged 15 - 19 years-old at five senior high schools across Jayapura Municipality area. Results according to chi-square statistical test provided correlated variables to age (p value = 0.047), religion (p value = 0.048), pocket money (p value = 0.000), socio-culture (p value = 0.001), tariff (p value = 0.047), staff (p value = 0.043), facility (p value = 0.046), knowledge (p value = 0.002), attitude (p value = 0.006). Furthermore, the logistic regression test resulted in staff, need, and domicile status as the most affecting variables on the use of the adolescent reproductive health. This research recommended that service staff had to be friendly and take account for confidentiality, to understand the development of the adolescence, either physically, psychologically, or socially, to provide adolescent reproductive health service at schools, and to have an open communication between adolescents and their parents in order to monitor their development. Key words: health services, PKPR, Student High Schools, Jayapura